PENGARUH DIVERSIFIKASI PRODUK PEMBIAYAAN TERHADAP PROFITABILITAS PERBANKAN SYARIAH DI INDONESIA - Asep Suryanto; Agus Ahmad Nasrulloh (Universitas Siliwangi, 2019)
This study aims to analyze the effect of mudharabah and murabahah financing on the level of profitability in Islamic banking, namely the Islamic Commercial Bank and Sharia Business Units registered with Bank Indonesia using the Return on Equity (ROE) ratio. The research method used is descriptive quantitative approach. The sample used was 30 data financing and profitability of Islamic banks for the period 2002-2013, by using purposive sampling technique. The method of collecting data uses documentation techniques. The tool of analysing data is used multiple regression analysis. The research result shows, mudharabah and murabahah financing are jointly affected by profitability, but partially mudharabah and murabahah financing does not affect Return On Equity. Simultaneously mudharabah and murabahah financing gives effect to Return On Equity, this is evidenced by the calculated F value (5.158) F table (3.35). Partially both mudharabah and murabahah financing do not have an effect on Return On Equity.